Crocins pattern in saffron detected by UHPLC-MS/MS as marker of quality, process and traceability. (30th October 2018) - Rocchi, R.; Mascini, M.; Sergi, M.; Compagnone, D.; Mastrocola, D.; Pittia, P.
Highlights: UHPLC-MS/MS method for the determination of crocins isomers and isoforms in saffron. Experimental design was applied to optimize extraction of crocins. Multivariate analysis to distinguish saffron samples by storage and process. Traceability can be obtained by crocins concentration and isomers pattern. Comparison with Quality evaluation of saffron by conventional indices (ISO 3632-1:2011). Abstract: This study was carried out to develop an UHPLC-MS/MS analytical procedure, to determinate all isomers and isoforms of crocins of 42 saffron samples, with different origin, age and dried using different process conditions. A preliminary experimental design was applied to optimize the extraction of crocins; UHPLC-MS/MS conditions were set to obtain the best analytical performances in terms of sensitivity and selectivity. The optimised conditions allowed to determine ten crocins; their amount in samples was significantly different and affected by process, age and origin. Drying conditions influenced the crocins pattern and this was particularly evidenced in the more recently produced samples, with a clear separation between mild and high thermally treated samples. Principal Component Analysis of all crocins data allowed to discriminate samples based on origin (Italy vs. other countries) and age. Results confirm the feasibility of the use of crocins pattern as marker of quality and traceability of saffron.